1992
DOI: 10.21236/ada248543
|View full text |Cite
|
Sign up to set email alerts
|

Tear Straps in Airplane Fuselage

Abstract: ,'m-nContract N00014-89-J-1276T r " r Abstract A procedure based on dynamic fracture mechanics is proposed for assessing the effectiveness of tear straps in a rupturing airplane fuselage weakened by a row of multiple site damage (MSD).A large deformation, elastic-plastic finite element model of the rupturing fuselage with an unsymmetrical crack flap is used to demonstrate the existence of a mixed mode I and II crack tip deformation and a large axial stress preceding the propagating crack.These numerical result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…13 and 14. These results show that the modified crack-kinking criterion of Kosai et al [5][6][7] can predict the crack-kinking locations and angles in full-scale tests equally well.…”
Section: Full-scale Fuselage Testsupporting
confidence: 53%
“…13 and 14. These results show that the modified crack-kinking criterion of Kosai et al [5][6][7] can predict the crack-kinking locations and angles in full-scale tests equally well.…”
Section: Full-scale Fuselage Testsupporting
confidence: 53%
“…Eventually, notice that a similar investigation to that shown was carried out in [18] by implementing the point stress criterion [15,16]. Nevertheless, results were presented considering a unique dimensionless T-stress, s ¼ T…”
Section: Ffm Resultsmentioning
confidence: 85%
“…Among these, the point stress criterion represents undoubtedly the simplest and most implemented approach. In the spirit of the works by Williams and Ewing [3] and Ritchie et al [15], it was put forward in [16,17] and later developed and applied to different experimental data in [18,19]. Nonlocal (average) stress and energy criteria were formalized by Seweryn [17] (see also [20] for considerations on the latter).…”
Section: Introductionmentioning
confidence: 99%
“…Critical distance r c has a significant effect on the crack initiation angle (Smith et al, 2001). For accurate determination of the crack propagation angle in metallic gears, appropriate value of parameter r c should be evaluated from experimental investigation (Kosai et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the cited research work considers only the influence of K I and K II stress intensity factors on crack propagation, which is a valid assumption for long cracks. Williams and Ewing (1972), Ueda et al (1983) and Kosai et al (1993) observed differences in crack initiation angles obtained by the MTS criterion and experiments. To account for the difference, they have modified the MTS criterion to incorporate constant term in the asymptotic stress field approximation series expansion around the crack tip, i.e.…”
Section: Introductionmentioning
confidence: 96%